Notes on the Economic Evaluation of Transport Projects : Fiscal Impacts - Mackie, Peter; Nellthorp, John; Laird, James (World Bank, Washington, DC, 2012)
The Economic Evaluation Notes are arranged in three groups. The first group (TRN-6 to TRN-10) provides criteria for selection a particular evaluation technique or approach; the second (TRN-11 to TRN-17) addresses the selection of values of various inputs to the evaluation, and the third (TRN-18 to TRN-26) deals with specific problematic issues in economic evaluation. The Notes are preceded by a Framework (TRN-5), that provides the context within which we use economic evaluation in the transport sector. Transport projects have an impact not only on citizens and businesses, but on governments - central, regional and local. Financing and managing the project will place demands on the government's capital and current accounts. Whether these demands are greater or smaller, and how they are phased over time, will depend on the financing mechanisms used and the extent to which the public sector is involved. Alternative approaches for private finance and management are described in the World Bank's 'Public-Private Options' toolkit. In this note, we consider how the appraisal should take the financial effects into account, and how they fit within the appraisal results, as described in the Framework.